2007
DOI: 10.1016/j.jacc.2006.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Delayed Enhancement by Magnetic Resonance Imaging in Patients With Muscular Dystrophy

Abstract: Cardiovascular magnetic resonance can identify MF and may be useful for detecting the early stages of cardiomyopathy in MD. Future work will be needed to evaluate whether CMR can influence cardiomyopathy and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
144
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(167 citation statements)
references
References 18 publications
15
144
0
8
Order By: Relevance
“…As such, it validates the concerns raised by both the European Neuro Muscular Center (ENMC) and AAP that: (1) affected individuals do not come to the attention of the cardiac specialist until late in the disease process when then clinical manifestations of cardiac dysfunction become evident; (2) echocardiographic and electrocardiographic screening of affected individuals at diagnosis and serially thereafter as recommended is minimal; (3) the use of cardiac therapies to potentially alter the course of cardiac involvement in affected individuals is limited; and (4) the evaluation of more sophisticated tools (i.e., cardiac magnetic resonance for fibrosis detection 18 ) to understand cardiovascular involvement in affected patients is currently limited but needed. 4,5 …”
Section: Limitations Of the Studymentioning
confidence: 99%
“…As such, it validates the concerns raised by both the European Neuro Muscular Center (ENMC) and AAP that: (1) affected individuals do not come to the attention of the cardiac specialist until late in the disease process when then clinical manifestations of cardiac dysfunction become evident; (2) echocardiographic and electrocardiographic screening of affected individuals at diagnosis and serially thereafter as recommended is minimal; (3) the use of cardiac therapies to potentially alter the course of cardiac involvement in affected individuals is limited; and (4) the evaluation of more sophisticated tools (i.e., cardiac magnetic resonance for fibrosis detection 18 ) to understand cardiovascular involvement in affected patients is currently limited but needed. 4,5 …”
Section: Limitations Of the Studymentioning
confidence: 99%
“…При заболеваниях, сопровождающихся выражен-ными нарушениями ритма, рекомендуется проведение суточного мониторирования ЭКГ. Также для оценки степени фиброза миокарда, воспалительных измене-ний, патологии перикарда у пациентов могут приме-няться такие неинвазивные методы диагностики, как магнитно-резонансная или компьютерная томо-графия сердца с контрастированием [13,14].…”
Section: лекции и обзорыunclassified
“…In female carriers an ECG and echocardiogram should be performed at diagnosis or after the age of 16 years and at least every 5 years thereafter, or more frequently in patients with abnormalities on investigation or carriers with severe skeletal muscle symptoms or cardiac symptoms. detect cardiac fibrosis in patients with Duchenne muscular dystrophy [12,13]. The study showed, that late gadolineum enhancement was negative related to left ventricular ejection fraction.…”
mentioning
confidence: 92%